An empirical examination of the extent of software process improvement in software SMEs. Issue 9 (3rd January 2013) - Clarke, Paul; O'Connor, Rory V.
SUMMARY: Although earlier studies revealed much about software process improvement (SPI) in software small‐ to medium‐sized enterprises (SMEs), no earlier research set out to determine the full extent of SPI being implemented in software SMEs. Therefore, this study was designed from the outset to elicit all instances of SPI, which we term SPI events – no matter how small or informal. We make the important new discovery that SMEs initiate a considerable amount of SPI, albeit in varying quantities in different organisations. No earlier study reported that the practice of SPI was so widespread in software SMEs, and this is perhaps related to the extensive scope of the enquiry adopted in this study. Our study also finds that the significant majority of SPI in software SMEs is minor or moderate in nature, sometimes leveraging the human capital via improvements in tacit knowledge. Software development is an intrinsically human intensive activity, and it therefore follows that the maximisation of the human capital in an organisation is a source of competitive advantage. However, contemporary process maturity frameworks and quality management standards do not fully exploit the capacity of human capital and may therefore diminish rather than improve the competitive advantage of software SMEs. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The study findings presented in this paper suggest that software process improvement (SPI) is implemented on a regular basis in small‐ to medium‐sized software development companies (software SMEs). Much of the reported SPI is minor or moderate in nature, often leveraging the power of human talent. The reported improvements in practice are not always considered by the practitioners themselves to be instances of SPI, even though they result in an improved work process.